Electrical Conductivity in Electrodeposited Cu-Ge(O) Alloy Films. Issue 13 (1st January 2018) - Zhao, Fu; Xu, Yin; Tumelero, Milton; Pelegrini, Silvia; Pasa, Andre; Zangari, Giovanni
Abstract : Integrated circuits currently use mainly copper as the interconnect material; unfortunately the ongoing miniaturization currently requires materials with higher electromigration resistance and possibly improved conductivity. In this context we report on the structure, microstructure and electrical properties of a series of Cu-Ge(O) alloy films, electrodeposited from an alkaline tartrate electrolyte. The composition of the films varies between zero and 20 at% Ge, with a significant incorporation of oxygen. Film morphology is dense and uniform, with Cu-Ge films exhibiting smaller apparent grain size (∼50 nm) with respect to Cu films grown from a similar electrolyte. Solid solutions and phase mixtures of a solid solution with the intermetallic are observed with increasing Ge fraction; the presence of intermetallic phases is confirmed by TEM imaging and diffraction. The resistivity of 50 nm thick films follows the published trend, with a slight increase of the value upon solid solution formation and a minimum in correspondence of the intermetallic composition. Thicker films (∼1 um) on the other hand show a different trend, with resistivity increasing with Ge and O at%; in this case the resistivity is probably dominated by the oxygen incorporation.